1994
DOI: 10.1111/j.1365-3180.1994.tb01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the concentrations of isoproturon and its degradation products in soil and soil solution during incubation at two temperatures

Abstract: Changes in the concentrations of [''*C]carbonylisoproturon and its degradation products in a clay-loam soil and in soil solution during incubation at 11°C and 18°C for 6 weeks, were measured following solvent extraction and soil solution sampling with glass microfibre filters. During herbicide degradation, ' "^CCh was released (up to 20%) and unextractable radioactivity increased (up to 30%). Monomethyl isoproturon was the main metabolite in soil followed by metabolite X5 (possibly hydroxy di-desmethyl isoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…In general, K d values increased with time for all soils under study, obtaining values by the range of 0.91-1.79 (after 1 day) and 3.15-4.77 mg l −1 (after 30 days) what would show up that not only the physicochemicals properties of soil would influence on increment of NFL adsorption, since the K d values obtained varied not only between the different soils but also with time. These increases in K d with time had been previously observed for a variety of pesticides such as atrazine and metolachlor [24], isoproturon [25], atrazine [26]. Imidacloprid sorption, as indicated by K d values, increased by a factor of 2.8 in three soils during a 16-week period [27,7], this fact was held to herbicide diffusion to less accessible or stronger binding sites with time.…”
Section: Adsorption-desorption Experimentsmentioning
confidence: 61%
“…In general, K d values increased with time for all soils under study, obtaining values by the range of 0.91-1.79 (after 1 day) and 3.15-4.77 mg l −1 (after 30 days) what would show up that not only the physicochemicals properties of soil would influence on increment of NFL adsorption, since the K d values obtained varied not only between the different soils but also with time. These increases in K d with time had been previously observed for a variety of pesticides such as atrazine and metolachlor [24], isoproturon [25], atrazine [26]. Imidacloprid sorption, as indicated by K d values, increased by a factor of 2.8 in three soils during a 16-week period [27,7], this fact was held to herbicide diffusion to less accessible or stronger binding sites with time.…”
Section: Adsorption-desorption Experimentsmentioning
confidence: 61%
“…Microbial degradation has been described as a primary mechanism responsible for IPU dissipation as well as other phenylurea herbicides from the soil (Fournier et al 1975;Gaillardon and Sabar 1994;Pieuchot et al 1996). In this study, it was observed that all nine soil samples collected from a field under rape seed/winter wheat/barley crop rotation, periodically exposed to IPU for 10 years, were able to mineralize about 40% of the 14 C-ring-labeled IPU initially added to 14 CO 2 after only 31 days of incubation.…”
Section: Discussionmentioning
confidence: 85%
“…Given these harmful effects, it is important to eliminate or minimize IPU contamination in soil and water. Microbial biodegradation, which is the primary mechanism for dissipating IPU as well as other phenylurea herbicides from the soil (Fournier et al 1975;Gaillardon and Sabar 1994;Pieuchot et al 1996), could prove a reliable, cost-effective remediation technique for IPU abatement. Several studies have reported the adaptation of soil microflora to IPU degradation in response to repeated exposure to this herbicide over a long period on fields under cultivation El-Sebai et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…6, step 1). MDIPU has previously been reported to be the main metabolite produced during the degradation of IPU in agricultural soils (4,6,13,16,19,22). An alternative metabolic pathway involving initial hydroxylation of the isopropyl side chain resulting in 2-hydroxy-IPU [3-(4-(2-hydroxyisopropyl)-phenyl)-1,1-dimethylurea] has also been described in agricultural soils (19,32).…”
Section: Discussionmentioning
confidence: 99%